2008
DOI: 10.1007/s00284-008-9239-0
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effects of Green Tea Polyphenols on Clinical Isolates of Methicillin-Resistant Staphylococcus aureus

Abstract: The antibacterial effects of tea polyphenols (TPP) extracted from Korean green tea (Camellia sinensis) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) were evaluated. Characterization of the minimal inhibitory concentration (MIC) of oxacillin for 30 S. aureus strains isolated from patients treated with oxacillin identified 13 strains with an oxacillin MIC C 4 lg/mL as methicillinresistant Staphylococcus aureus (MRSA) (range: 8 to 512 lg/ mL), while 17 strains were methicillin-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 23 publications
(22 reference statements)
4
34
1
Order By: Relevance
“…Green tea was also reported to have a synergistic effect with β-lactam antibiotics against MRSA [24][25][26][27][28] , It was also reported that the main component of tea polyphenols, epigallocatechin gallate can reverse methicillin resistance of MRSA by inhibiting the synthesis of PBP2 [29] , Epigallocatechin gallate not only increases the activity of β-lactams but also increases the activity of non-β-lactam cell wall biosynthesis inhibitors [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Green tea was also reported to have a synergistic effect with β-lactam antibiotics against MRSA [24][25][26][27][28] , It was also reported that the main component of tea polyphenols, epigallocatechin gallate can reverse methicillin resistance of MRSA by inhibiting the synthesis of PBP2 [29] , Epigallocatechin gallate not only increases the activity of β-lactams but also increases the activity of non-β-lactam cell wall biosynthesis inhibitors [26] .…”
Section: Discussionmentioning
confidence: 99%
“…There are some other studies concluding that tea extracts may have potent antibacterial effects in vivo and in vitro against a wide range of pathogenic bacteria, including antibiotic-resistant strains. [9][10][11]18,21] Black tea extract has been found to be more effective against gram-positive bacteria such as S. aureus Haemophilus aphrophilus, Bacillus cereus, e.g., then gram-negative bacteria. The reason for this is lipopolysaccharides in the outer membrane of gram negative bacteria prevent penetration.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Black tea extracted with eight different solvents, includes polyphenol contents which exhibit antibacterial and antioxidant activity against several types of pathogenic bacteria, including Vibrio cholerae, Escherichia coli, Shigella, Salmonella, and S. aureus. [9][10][11] Both in vivo and in vitro studies have demonstrated that tea or tea-based extracts have antimicrobial properties when applied topically. [12,13] But it is not clear whether or not tea exhibits the same antimicrobial activity when consumed orally as beverage.…”
mentioning
confidence: 99%
“…The stress shock proteins were analyzed by SDS-PAGE (A), and western blot with anti-DnaK (B), and anti-GroEL (C) monoclonal antibodies, respectively. 에 의하여 세포에 독성이 있다는 것을 보여준 바 있다 (Park et al, 2001;Cho et al, 2002Cho et al, , 2007Cho et al, , 2008Chang et al, 2004 …”
Section: Tpp 노출에 따른 세포 지방산 조성 변화mentioning
confidence: 99%